Assessment on language rights in education domain: shift-oriented, maintenance-oriented or something else?. Issue 1 (2nd January 2016) - Ping, Wang
Abstract : There is a trend towards the shift of the Uyghur language as the language of instruction in schools in the Xinjiang Uyghur Autonomous Region of China. This article presents several examples of such a shift first and then it reviews the concept of language rights (LR) and applies them to the current situation of the Uyghur language in education domain. After that it presents and discusses some reasons to address a pressing concern of the LRs in Xinjiang in accordance with China's domestic conventions as well as with some international conventions. In the end, it introduces the concept of language ecology on the basis of legally binding LRs as an ideal outlet for the Uyghur language in Xinjiang.